2021
DOI: 10.1177/21514593211006692
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 Negative Hip Fracture Patients During the Acute and Subacute Pandemic

Abstract: Objectives: To better elucidate how the COVID-19 pandemic has affected the operatively treated geriatric hip fracture population and how the health care system adapted to pandemic dictated procedures. Design: Retrospective cohort study. Setting: A community hospital. Participants: Individuals ≥65 years of age presented with a proximal femoral fracture from a low-energy mechanism undergoing operative treatment from January 17, 2020 to July 2, 2020 (N = 125). Measurements: We defined 3 phases of healthcare syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…In comparison with previously reported data on hip fractures during the COVID-19 pandemic in an elderly population at a community hospital, [ 18 ] there were no statistically significant differences in demographics or comorbidities between patients at the trauma center and patients at the community hospital (data not shown). In contrast to our findings from the level 1 trauma center, the authors found that TTS and LOS increased during the pandemic in the community hospital.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…In comparison with previously reported data on hip fractures during the COVID-19 pandemic in an elderly population at a community hospital, [ 18 ] there were no statistically significant differences in demographics or comorbidities between patients at the trauma center and patients at the community hospital (data not shown). In contrast to our findings from the level 1 trauma center, the authors found that TTS and LOS increased during the pandemic in the community hospital.…”
Section: Resultsmentioning
confidence: 45%
“…The length of stay varied widely around the world during the pandemic. Some studies report an increased LOS during the COVID-19 pandemic, [ 18 , 35 ] while others found a decreased LOS, [ 10 , 24 ] or no significant difference between periods. [ 9 , 33 ] We attribute these wide-ranging results to differing hospital-by-hospital protocols and workload effects of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicated that late presentation and delayed surgery increased complications and 30-day mortality. 39,40 In our study, the length delay of presentation with hip fractures in the elderly was 7 days, and we encountered postoperative infection and no mortality. Our sample was too small for us to make a conclusion regarding this matter.…”
mentioning
confidence: 55%